IS GENDER IMPORTANT TO FIRM PERFORMANCE? EVIDENCE FROM BUSY CEO - Ricky Ricky; Wisnu Yuwono; Robin Robin (Program Studi Akuntansi FPEB UPI, 2022)
This study investigates whether CEO busyness have an impact on company performance,and if this relationship is moderated by female CEOs by analyzing all company sectors apart from finance, insurance, and property that are included in the Kompas 100 index listed on the Indonesia Stock Exchange (IDX) in the 2017-2020 period. Our findings have shown that the presence of a busy CEO will cause a decrease in company performance. In addition, we also found that negative relationship is stronger in companies whose CEOs are female. For firms and shareholders,our findings indicate that it is not a good idea for CEOs to hold more than one outside directorships, especially those who occupy the position of CEO are female. Our results suggest that restrictions on CEO busyness would be beneficial to shareholders.